Thalamic neuromodulation and its implications for executive networks - Varela, Carmen (Frontiers in Neural Circuits, 2014)
The thalamus is a key structure that controls the routing of information in the brain. Understanding modulation at the thalamic level is critical to understanding the flow of information to brain regions involved in cognitive functions, such as the neocortex, the hippocampus, and the basal ganglia. Modulators contribute the majority of synapses that thalamic cells receive, and the highest fraction of modulator synapses is found in thalamic nuclei interconnected with higher order cortical regions. In addition, disruption of modulators often translates into disabling disorders of executive behavior. However, modulation in thalamic nuclei such as the midline and intralaminar groups, which are interconnected with forebrain executive regions, has received little attention compared to sensory nuclei. Thalamic modulators are heterogeneous in regards to their origin, the neurotransmitter they use, and the effect on thalamic cells. Modulators also share some features, such as having small terminal boutons and activating metabotropic receptors on the cells they contact. I will review anatomical and physiological data on thalamic modulators with these goals: first, determine to what extent the evidence supports similar modulator functions across thalamic nuclei; and second, discuss the current evidence on modulation in the midline and intralaminar nuclei in relation to their role in executive function.